2008
DOI: 10.1007/s00330-008-1197-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MRI, 64-slice MDCT and DSCT in assessing functional cardiac parameters of a moving heart phantom

Abstract: To compare magnetic resonance imaging (MRI), 64-slice multi-detector computed tomography (MDCT) and dual-source computed tomography (DSCT) in assessing global function parameters using a moving heart phantom. A moving heart phantom with known volumes (215–258 ml) moving at 50–100 beats per minute was examined by three different imaging modalities using clinically implemented scanning protocols. End-diastolic and end-systolic volumes were calculated by two experienced observers using dedicated post-processing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…In this study, 3D cardiac CT data were used for ventricular volumetry rather than 2D cardiac MRI data in order to take advantage of a 3D threshold-based segmentation approach. 3D cardiac CT data were frequently downgraded to reformatted 2D data in previous studies [1,[6][7][8][21][22][23]. Compared with MRI ventricular volumetry, CT ventricular volumetry tends to overestimate ventricular volumes [20,23].…”
Section: Discussionmentioning
confidence: 98%
“…In this study, 3D cardiac CT data were used for ventricular volumetry rather than 2D cardiac MRI data in order to take advantage of a 3D threshold-based segmentation approach. 3D cardiac CT data were frequently downgraded to reformatted 2D data in previous studies [1,[6][7][8][21][22][23]. Compared with MRI ventricular volumetry, CT ventricular volumetry tends to overestimate ventricular volumes [20,23].…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, spatial resolution obtained with contemporary CT techniques surpasses spatial resolution of MRI acquisitions. A recent phantom study, comparing functional assessment with MRI and DSCT, showed that DSCT measurements deviated less from the real phantom volumes than MRI measurements [12]. MRI structurally overestimated EDV and ESV, resulting in a systemetic underestimation of LVEF.…”
Section: Discussionmentioning
confidence: 97%
“…A reliable measurement of LV functional parameters with MDCT compared with other known non-invasive techniques, including the reference standard provided by magnetic resonance imaging (MRI), was shown previously [9][10][11]. A recent phantom study comparing functional assessment with MRI and DSCT actually showed that DSCT measurements deviated less from the real phantom volumes than MRI measurements [12].…”
Section: Introductionmentioning
confidence: 97%
“…With the continuous improvement of time and spatial resolution in MSCT, multi-slice spiral CT coronary artery angiography (MSCTCA) could be used for the evaluation of coronary arterial stenosis, and the original data could also be used for a one-stop cardiac function determination. Studies have shown that 64-layer SCTCA has high sensitivity and specificity in the diagnosis of coronary artery stenosis, and its results for cardiac function parameters were found to be highly correlated with the gold standard cMRI (Annuar et al, 2008;Groen et al, 2009;Zhang et al, 2009;Ito et al, 2010). In the present study, 128-layer SCTCA was used, along with retrospective ECG gating techniques (Mollet et al, 2005;Lu et al, 2008), to continuously scan several cardiac cycles, and the real-time dynamic 4-D raw image data of the systolic and diastolic ends, namely the "time-space" periods, were analyzed for the one-stop noninvasive evaluation of coronary artery stenosis, left ventricular structure and systolic function (Ko et al, 2010;Takx et al, 2012).…”
Section: Introductionmentioning
confidence: 99%